Rare Species of Katarniyaghat Wild Life Sanctuary, District Bahraich, Uttar Pradesh, India - Maliya, S. D. (Indian Forester, 2007)
The paper presents a local assessment of rare species of Katarniyaghat Wildlife Sanctuary of District Bahraich (Uttar Pradesh). Taking regular visits in different seasons, 41 rare species have been recorded in the sanctuary region. Twenty three species of the total number of rare species have a wide range of Ayurvedic and Ethnomedicinal uses. Remaining 18 species are economically valuable and frequently used by local inhabitants for their day to day requirements.